Review of metastasis to meningiomas with case examples - Magnus Sættem; Terje Sundstrøm; Anna.K.Myrmel Sæle; Rupavathana Mahesparan (Brain and Spine)
Introduction: A tumor-to-tumor metastasis (TTM) is a rare metastatic process where a primary malignant tumor metastasizes to another tumor, most commonly a benign tumor such as a meningioma. Here, we present two recent cases of tumor-to-meningioma metastases (TMM) from our clinical practice and review of recent literature. The primary cancers were prostate and breast cancer, respectively. Material and methods: We reviewed the electronic medical records of the two patients and conducted a literature review of TTM, focusing on biological mechanisms related to TMM. Results: Our first patient, a man with a history of stable prostate cancer, underwent resection of two WHO grade 1 meningiomas, and the largest tumor was found to have TMM. Our second patient, a woman with progressive breast cancer, was operated for a WHO grade II meningioma, and the meningioma harbored breast cancer metastases. TMM is a rare occurrence, but breast cancer is a much more frequent cause than prostate cancer and we reviewed 50 cases. Only 15 of cases of TMM from prostate cancer have been described. Discussion and conclusion: TMM is a rare phenomenon, but it is important to be aware of this as more and more patients live with cancer and meningiomas have a high prevalence, The possibility of TMM may impact not only both the surgical and oncological treatment but also surveillance of incidental meningiomas.